2011 IEEE International Conference on Multimedia and Expo 2011
DOI: 10.1109/icme.2011.6012148
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual quantitative quality assessment of JPEG2000 compressed ct images with various slice thicknesses

Abstract: Modern medical equipments produce huge amounts of data that need to be archived for long periods and efficiently transferred over networks. Data compression plays an essential role in reducing the amount of medical imaging data. Medical images can usually be compressed by a factor of three before any degradation appears. Higher compression levels are desirable but can only be achieved with lossy compression, thus scarifying image quality. The diagnosis value of compressed medical images has been studied and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Pambrun et al in [47] study the quality assessment of compressed CT images. They present the diagnosis of compressed medical images and recommend the maximum acceptable compression ratios based on qualitative visual analysis.…”
Section: Quasi-subjective Pdoqmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pambrun et al in [47] study the quality assessment of compressed CT images. They present the diagnosis of compressed medical images and recommend the maximum acceptable compression ratios based on qualitative visual analysis.…”
Section: Quasi-subjective Pdoqmsmentioning
confidence: 99%
“…Such a need is especially clear for [45] approaches were used to with PSNR correlate with MOS and WSNR A. Przelaskowski Used MSE, PSNR, The proposed [46] Picture Quality Scale distortion metrics showed a to correlate MOS correlation of 0.9 J. Pambrun, Used VSNR to correlate VSNR showed et al [47] subjective scores for a high correlation JPEG 2000 K. J. Kim, Used various objective metrics HDR-VDP metric et al [48] with subjective metrics is best correlated Di Lin, Used for multiple Reached to a et al [49] diagnosis purposes correlation of 0.98 elderly patients: several studies have shown that about half of people 65 years or older have a comorbid condition [33]. Thus, in [49], an image quality metric (defined as metric for comorbidity, IF C) applicable for multiple diagnosis purposes is proposed, and it is able to assess how well a medical image can be used for the diagnosis on a comorbid patient's conditions as well as on a single disease of this patient.…”
Section: Quasi-subjective Pdoqmsmentioning
confidence: 99%